The Effectiveness of the Counter Pressure and Endorphin Massage Techniques for Managing First-Stage Labor Pain in Childbearing Women at the Tangerang City Maternity Clinic - Siti Maisaroh; Dewi Susanti; Samsinar Samsinar (Lembaga Publikasi Ilmiah Nusantara, 2026)
Labor pain during the first stage of childbirth is a complex physiological and psychological experience that may negatively affect maternal outcomes if not properly managed. This study aimed to determine the effectiveness of combined counter-pressure and endorphin massage techniques in reducing labor pain among childbearing women in Tangerang City. A quasi-experimental pretest–posttest control-group design was used with 30 parturient women, divided into an intervention group (n = 15) and a control group (n = 15). Pain intensity was measured using the McGill Pain Questionnaire before and after treatment. The intervention group received counter-pressure and endorphin massage during uterine contractions, while the control group received standard care. Data were analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test (p < 0.05). Results showed a significant reduction in pain intensity in the intervention group (p = 0.000), while no significant change was found in the control group (p = 1.000). Pain scores in the intervention group decreased from severe to moderate levels. In conclusion, combined counter-pressure and endorphin massage techniques are effective, safe, and low-cost non-pharmacological interventions for reducing first-stage labor pain. They may improve maternal comfort, especially in low-resource settings.